Diversity of Endophytic Actinomycetes Isolated from Roots and Root Nodules of Pueraria candollei Grah. ex Benth. and the Analyses of Their Secondary Metabolites - Panitch Boonsnongcheep (Science Faculty of Chiang Mai University, 2019)
Pueraria candollei Grah. ex Benth. is a Thai herb that contributes to many phytoestrogenic-related pharmacological activities. In this study, the diversity of endophytic actinomycetes from roots and root nodules of P. candollei and actinomycetes from rhizospheric soils were investigated. Moreover, the secondary metabolites production of these isolated actinomycetes was investigated. A total of 85 isolates were obtained from roots, root nodules and rhizospheric soils, 32 from the roots of P. candollei var. candollei, 26 from the root nodules of P. candollei var. mirifica and 27 from rhizospheric soil samples. Partial 16S rRNA sequence data revealed that the isolated actinomycetes were distributed among 7 genera including, Streptomyces, Micromonospora, Verrucosispora, Microbispora, Nonomuraea, Plantactinospora and Shimazuella. The majority of isolates from plant sources were members of the genus Micromonospora. Broth extracts of these isolates were analyzed using LC/UV and LC/MS. The physicochemical properties of 10 selected peaks were searched in the database. The physicochemical properties of some peaks were matched with known microbial metabolites. The structure of an unknown compound was elucidated using spectroscopic data. The NMR data indicated the presence of N-acetylhomocysteine moiety and the compound was determined to be S-adenosyl-N-acetylhomocysteine. This compound was isolated from Micromonospora for the first time. In conclusion, this work contributed to the known information on the diversity of actinomycetes associated with P. candollei and their capability for secondary metabolite production.